Investigation and Analysis of the Role of Mines in the Economic and Political Development of Afghanistan - Aburagheb Amani; Mohammad Asif Gardezi (International Journal of Social Science and Humanity, 2025)
Afghanistan, often called a "geological treasure trove," is richly endowed with vast mineral deposits worth over $3 trillion. The minerals, including copper, lithium, iron, gold, and rare earths, can be used to resurrect the nation's economy, reduce dependence on foreign aid, and bring about political stability. However, three decades of conflict, political turmoil, corruption, and inadequate infrastructure have been a hindrance to the effective exploitation of the resources. This paper examines the role of mining in Afghanistan's economic and political development, distilling the opportunities and challenges in the industry. Drawing on comparative case studies from resource-rich countries like Botswana and Chile, the study highlights the importance of open government, robust regulatory institutions, and strategic foreign partnerships. The evidence suggests that an efficiently operated mining sector would be a driver of sustainable development, provided that Afghanistan addresses deep-seated systemic evils in the form of corruption, insecurity, and environmental degradation. The research concludes with policy imperatives aimed at maximizing the contribution of the sector to national development.